Kidney Donor Profile Index Is a Reliable Alternative to Liver Donor Risk Index in Quantifying Graft Quality in Liver Transplantation. Issue 12 (December 2019) - Scheuermann, Uwe; Truong, Tracy; Seyferth, Elisabeth R.; Freischlag, Kyle; Gao, Qimeng; Yerxa, John; Ezekian, Brian; Davis, Robert P.; Schroder, Paul M.; Peskoe, Sarah B.; Barbas, Andrew S.
Abstract : Background: The most established metric for estimating graft survival from donor characteristics in liver transplantation is the liver donor risk index (LDRI). The LDRI is calculated from donor and transplant-related variables, including cold ischemic time. Because cold ischemic time is unknown at the time of organ offer, LDRI is not available for organ acceptance decisions. In contrast, the kidney donor profile index (KDPI) is derived purely from donor variables known at the time of offer and thus calculated for every deceased donor in the United States. The similarity in donor factors included in LDRI and KDPI led us to hypothesize that KDPI would reliably approximate LDRI in estimating graft survival in liver transplantation. Methods: The United Network of Organ Sharing registry was queried for adults who underwent deceased donor liver transplantation from 2002 to 2016. The cohort was divided into quintiles of KDPI and LDRI, and graft survival was calculated according to Kaplan Meier. Hazard ratios for LDRI and KDPI were estimated from Cox proportional hazards models, and Uno's concordance statistic was compared. Results: In our analysis of 63 906 cases, KDPI closely approximated LDRI in estimating liver graft survival, with an equivalent concordance statistic of 0.56. Conclusions: We conclude that KDPI can serve as a reasonable alternative to LDRI in liver acceptance decisions.